2012
DOI: 10.1155/2012/517424
|View full text |Cite
|
Sign up to set email alerts
|

Acute Generalized Exanthematous Pustulosis due to Tocilizumab in a Rheumatoid Arthritis Patient

Abstract: We report a female patient with rheumatoid arthritis which was refractory to methotrexate, leflunomide, and anti-TNF therapy. She was treated with anti-IL-6 tocilizumab (TCZ), with an early appearance of sterile pustules on erythematous swollen skin of trunk, back, and abdominal area. The lesions were consistent with the diagnosis of acute drug-related generalized exanthematous pustulosis (AGEP). This adverse event was controlled with medical treatment without requiring removal of TCZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…A previous case report by Wendling et al [5] reported de novo psoriasis in a patient with seronegative RA raising the possibility that this was a new development of psoriasis in a psoriatic arthritis case [2,4,5]. To the best of our knowledge this is the first case report of TCZ psoriasis in an auto-antibody-positive RA case.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A previous case report by Wendling et al [5] reported de novo psoriasis in a patient with seronegative RA raising the possibility that this was a new development of psoriasis in a psoriatic arthritis case [2,4,5]. To the best of our knowledge this is the first case report of TCZ psoriasis in an auto-antibody-positive RA case.…”
Section: Discussionmentioning
confidence: 67%
“…With specific reference to TCZ-induced psoriasis a number of cases have been reported. One of the patients [13] has still disease and the other has RA [4], with exacerbation of pre-existing psoriasis within 2 weeks after the first infusion of TCZ, while 1 patient developed de novo psoriasis [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discontinuance of tocilizumab and topical administration of corticosteroids rapidly improved the skin condition within 4 weeks, along with normalization of eosinophil ratio. To date, a few kinds of adverse skin reactions due to tocilizumab have been reported, including psoriasis erythroderma, papular eruptions and acute generalized exanthematous pustulosis (AGEP), some of which contain pustules. By contrast, although small pustular lesions were also intermingled with vesicles in our case, diffuse erythrodermic conditions were not recognized.…”
mentioning
confidence: 99%
“…Tocilizumab inhibits signaling from the IL‐6/IL‐6 receptor, which may induce a cytokine imbalance, possibly mediated via regulatory T cells . Alternatively, neutrophils are activated by tocilizumab by some mechanisms which are involved in the induction of some of the above skin rashes . Further accumulation of similar cases and studies are warranted.…”
mentioning
confidence: 99%